Vkhodʺ vʺ Unskui︠u︡ gubu / Sostavleno vʺ 1899 godu po rabotamʺ otdi︠e︡lʹnoĭ sʺemki Bi︠e︡lago mori︠a︡ 1898 goda - Soviet Union. Gidrograficheskoe upravlenie (Leningrad : Morskoe ministerstvo, Glavnoe gidrograficheskoe upravlenie SSSR; [Ленинград] : Морское министерство, Главное гидрографическое управление СССР, 1924)
"Masshtabʺ 1/21000 ili 250 sazh. 7-ti futovoĭ mi︠e︡ry vʺ di︠u︡ĭmi︠e︡" = Scale 1/21000 or 250 7-foot fathoms in 1 inch.; Relief shown by hachures. Depths shown by soundings and isolines.; Main title translation: Entrance in Unskaya Bay.; Top margin title translation: White Sea, Dvina Bay.; Greenwich meridian.; Includes illustrations of light houses, 2 views of coastlines and text.; "No. 538" -- margins Color; 1:21,000